Optimal Organic Fertilizer Rates for Greenhouse Production of Container Fresh Herbs. Issue 2 (19th January 2019) - Sun, Qian; Qian, Yun; Wang, Jianzhu; Migliaccio, Kati W.; Olczyk, Teresa; Li, Yuncong C.
ABSTRACT: There is minimal published research information on optimal fertilizer rates for growing organic herbs in a greenhouse container system under warm climate in south Florida. Our objective was to determine the optimum organic fertilizer rate for container herb production in a greenhouse for basil ( Ocimum basilicum), coriander ( Coriandrum sativum ), and dill ( Anethum graveolens ) using Perdue certified organic fertilizer (Agri Recycle, 4–2-3, Seaford, DE) (4N-0.85P-0.25K). The organic fertilizer was mixed with potting medium (Fafard, Conrad Fafard, Inc.; Agawam, MA) at four rates: 0, 10.6, 21.1, and 31.7 g of fertilizer per L of potting medium. Results indicated an increase in nitrogen in plant tissue with an increase in fertilizer rate for all herbs and both trials. Based on statistical results from the fresh and dry weights of the herbs, the Purdue fertilizer rate for optimum production should be between 21.1 and 31.7 g of fertilizer per L of potting media. The lower fertilizer rate (21.1 g) is more attractive for overall production since it would result in a lower cost than using the 31.7 g fertilizer rate. This recommendation is based on the fertilizer chosen, the herb, the potting media, and the location of this study.